Public international law a multi-perspective approach - Hauck, Sué González; Kunz, Raffaela; Milas, Max (Routledge, 2024)
Public International Law: A Multi-Perspective Approach is a comprehensive yet critical introduction to the diverse field of public international law. Bringing together a unique range of perspectives from around the world and from different theoretical approaches, this textbook introduces both the overarching questions and doctrines of public international law, as well as the specialised sub-fields. These include emerging fields such as international law in cyberspace, international migration law, and the international climate regime. The book includes numerous case examples, references to debates and controversies in the literature, and focus sections addressing topics in more depth. Featuring an array of pedagogical features, including learning objectives, suggested further reading and resources, and QR codes to interactive exercises, this book is ideal for students studying this field for the first time and also offers something new for students who would like to deepen their knowledge via a diverse and engaging range of perspectives. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-ShareAlike (CC-BY-SA) 4.0 License.
Keywords: International law.; LAW / General